The Marche: Italy's new frontier for international retirement migration. Issue 5 (5th April 2019) - King, Russell; Cela, Eralba; Morettini, Gabriele; Fokkema, Tineke
Abstract: Within the linked fields of population, migration, and ageing, international retirement migration (IRM) has emerged as a strong focus for empirical research. Thus far, the classic studies have been on European North–South IRM, with a specific concentration on iconic regions such as the Costa del Sol, southern France, and Tuscany. But the geography of IRM is constantly changing, as prior destination regions become "saturated" and perhaps too expensive, so that new "frontiers" are opened up. One such frontier is the Italian region of Marche, now seen as a cheaper and more "authentic" region than Tuscany. This paper uses interview narratives from 69 older age British, Dutch, and German people who have relocated, as either permanent settlers or seasonal residents, in the Marche, in order to answer two questions. The questions relate first to the main drivers of IRM at the decision‐making level and, second, to the experiences of living there, including advantages and disadvantages. We find the participants for the most part engaged in active ageing, growing their own produce, and joining in local community life and are appreciative of the beauty of the hilly landscape. However, "full" integration is hampered by language and cultural barriers, whereas the bureaucracy is their main complaint.